E o homem que murmura contra o ensinamento secreto da Yahad será expulso e não mais voltará (1QS 7:17): a expulsão na comunidade judaica do mar Morto - Vieira, Fernando Mattiolli [UNESP] (2014)
In 1947, in the caves of the Judean desert, one of the greatest archaeological discoveries of the history was made, the greatest of ancient texts, known as Dead Sea Scrolls. Hundreds of texts were found, many of them assigned by researchers to a Jewish religious group who has lived not far from Jerusalem between 2 B.C. and 1 A.D. The initial discussions of this work will seek to address the problems related to their origin and the group that owned them. These discussions resulted in the use of the name Yahad to designate the group around these texts. In this manner, the necessary base is created so the object of this research can be worked: the expulsion in the Yahad. The sources show that this religious group made a striking innovation in the way of punishing individuals in that society, applying the expulsion to the transgressors instead of using known penalties such as those suggested in their sacred old books. To understand the operation of the practice of expulsion is of paramount importance to understand the limits of the group, the relationship of its internal social structure with the society in which it originated. After the key points about the practice of expulsion in the Yahad are elucidated, it will be possible to take a more ambitious proposal. It aims to explain no more the operation and the characteristics of the expulsion, but their origin and relationship with the entire Jewish society of the period. To do so, it uses the theoretical and methodological principles of the German sociologist Norbert Elias. By using them, it is possible to glimpse the social changes that have occurred in that society based on a long duration, which considers the past and the social transformations that have taken place until the period in which this group created the expulsion. To reinforce the conclusions that show the relationship between the birth of the expulsion in the Yahad and the society of that time, it is also considered ...